Analisis Analisis financial performance dan firm value perusahaan sektor industri logam di Indonesia - Yuniep Mujati Suaidah (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2020)
This study aims to determine the direct effect of capital structure, CSR and financial performance on firm value, and to determine whether financial performance can be a mediating variable between capital structure and CSR on firm value. This study uses secondary data, data collection with documentation on metal industrial sector manufacturing companies in the Indonesia Stock Exchange (IDX), as many as 14 companies were used as research samples with purposive sampling method, for 4 years so that the sample used 56 financial reports. Measurement of capital structure variables using DER, CSR with GRI-G4 guidelines, financial performance with ROA, firm value with PBV. Hypothesis testing using Path Anaysis. The results showed that capital structure had a positive and insignificant effect on financial performance, CSR had a significant positive effect on financial performance, and capital structure had a significant positive effect on firm value. CSR has a positive and insignificant effect on firm value, financial performance has a significant negative effect on firm value. The financial performance variable is not a mediating variable between capital structure and firm value, but is a mediating variable between CSR and firm value.